2006
DOI: 10.1007/s10529-006-0033-4
|View full text |Cite
|
Sign up to set email alerts
|

Betaine Tripled the Volumetric Productivity of d(-)-lactate by Escherichia coli Strain SZ132 in Mineral Salts Medium

Abstract: Osmotic stress restricts glycolytic flux, growth (rate and yield), D-lactate productivity, and D-lactate tolerance in Escherichia coli B strain SZ132 during batch fermentation in mineral salts medium with 10% (w/v) sugar. Addition of 1 mM: betaine, a non-metabolized protective osmolyte, doubled cell yield, increased specific productivity of D-lactate and glycolytic flux by 50%, and tripled volumetric productivity (from 8.6 to 25.7 mmol l(-1) h(-1); 0.8 to 2.3 g l(-1) h(-1)). Glycolytic flux and specific produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 15 publications
(16 reference statements)
2
38
0
Order By: Relevance
“…Zhou et al (2006) reported that d-())-lactate synthesis significantly increased when betaine was added to the culture medium as an osmoprotectant. It was likewise found that modification of the trehalose content in recombinant E. coli also resulted in higher growth (Purvis et al 2005), and trehalose-dependent stress tolerance was identified as a relevant trait for industrial purposes involving baker's yeast (Attfield 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al (2006) reported that d-())-lactate synthesis significantly increased when betaine was added to the culture medium as an osmoprotectant. It was likewise found that modification of the trehalose content in recombinant E. coli also resulted in higher growth (Purvis et al 2005), and trehalose-dependent stress tolerance was identified as a relevant trait for industrial purposes involving baker's yeast (Attfield 1997).…”
Section: Discussionmentioning
confidence: 99%
“…All controlled batch bioreactor studies were performed with defined minimal medium containing 3.5 g/liter of KH 2 PO 4 , 5.0 g/liter of K 2 HPO 4 , 3.5 g/liter of (NH 4 ) 2 HPO 4 , 0.25 g/liter of MgSO 4 ⅐ 7H 2 O, 15 mg/ liter of CaCl 2 ⅐ 2H 2 O, 0.5 mg/liter of thiamine, 0.12 g/liter of betaine, 1 ml/liter of a stock trace metal solution, 40 g/liter of glycerol (unless otherwise specified), and 10 g/liter of tetracycline (adapted from media described previously [6,21,26] 4 ) citrate. The first three salt components of the defined minimal medium were autoclaved, while the other components were sterile filtered and added to bioreactors.…”
Section: Methodsmentioning
confidence: 99%
“…Because the accumulation of pyruvate in our current study would simultaneously require the accumulation of K ϩ (or another counterion) to maintain the pH, we conducted an experiment to determine whether the addition of the known osmoprotectant betaine (38,50) would improve pyruvate accumulation. Without betaine present in the medium under acetate-limited conditions, strain ALS929 was able to accumulate over 56 g/liter pyruvate in about 28 h (Fig.…”
Section: Growth-limiting Nutrientmentioning
confidence: 99%
“…Another explanation for the observed termination of cell growth and pyruvate formation is the high osmotic stress caused by the K ϩ ion required to maintain the pH. Organic osmolytes, such as betaine, often accumulate naturally to protect cells from high osmotic stress (44), and the production of ethanol (38) and lactate (50) has been improved by the addition of betaine to the medium. Our fed-batch results similarly demonstrated that 5 mM betaine prolonged cell growth and thereby increased the final pyruvate concentration by at least 25%.…”
Section: Vol 74 2008mentioning
confidence: 99%